Strain Engineering of Energy Storage Performance in Relaxor Ferroelectric Thin Film Capacitors. Issue 6 (16th March 2022) - Xu, Shiqi; Shi, Xiaoming; Pan, Hao; Gao, Rongzhen; Wang, Jing; Lin, Yuanhua; Huang, Houbing
Abstract: Dielectric energy storage capacitors are receiving a great deal of attention owing to their high energy density and fast charging–discharging speed. The current energy storage density of dielectrics is relatively low and cannot meet the requirements of miniaturization of pulsed power equipment. Therefore, increasing the energy storage density of dielectrics has become a research hotspot. Herein, using phase‐field simulations to design polymorphic nanodomains, the strain engineering of energy storage performance of binary and ternary solid solution relaxor ferroelectric films is investigated. The results show that the energy storage performance of the ternary film is better than that of the binary film due to the polymorphic nanodomains. In addition, as the film in‐plane strain is modified from −2% to 2%, the energy density is improved by 80%, and the efficiency also increases from 52% to 77%. This work proves the remarkable energy storage performance of polymorphic films and provides a theoretical basis to optimize the energy‐storage performance of ferroelectric thin‐film capacitors by adjusting the misfit strain. Abstract : Theoretical calculations show that the energy storage performance of the ternary film is better than that of the binary film due to the polymorphic nanodomains. Through applying misfit strain, the performance can be further improved. The results provide a theoretical basis to optimize the energy‐storage performance of polymorphic thin‐film capacitors.